Effect of plant spacing and pruning on vegetative growth, yield and fruit quality of introduced mango cultivars - Ahmed, Tawhida B.M; Elkashif, Mohamed E; Elamin, Osman M (Gezira Journal of Agricultural Science, 2014)
Kitchener is the most extensively cultivated mango cultivar in the Sudan. However, this cultivar is not popular in export markets due to its high fiber content. Hence, internationally popular mango cultivars have been recently introduced to the Sudan from South Africa. They  include Tommy Atkins, Kent, Keitt, Haden and Sensation. An experiment was conducted in Kamleen nursery, Gezira State, Sudan, during June 2008 to May 2011, to investigate the effects of plant spacing and pruning on vegetative growth, yield and fruit quality of these introduced mango cultivars compared to the local cultivar, Abusamaka . The trees were planted at a spacing of 5x5m and 10x10 m and subjected to three types of pruning, namely, pruning to two branches, three branches, tip pruning and control. Treatments were arranged in a split-plot design with three replicates. Plant spacing was assigned to the main plots and pruning treatments to the sub-plots. Results showed that the wider spacing resulted in significantly larger canopy diameter and larger number of fruits per tree than the closer spacing in all cultivars and seasons. However, the closer spacing resulted in significantly larger number of fruits/ha and  higher total yield/ha than the wider spacing due to the larger number of trees/ha. Pruning of mango trees to three main branches resulted in significantly the highest yield components and total yield, followed by two branches, tipping and the lowest yield components were produced by the un-pruned control. The introduced mango cultivars had significantly more vigorous vegetative growth, earlier in flowering, higher yield components and total yield and better fruit quality than the local cultivar Abusamaka. It could be concluded that the introduced cultivars Tommy Atkins, Kent and Keitt are promising cultivars to be grown in the Sudan using the high density planting system and pruned annually for high production of good quality fruit.        يعتبر الصنف كتشنر أكثر أصناف المانجو انتشاراً في السودان ولكنه غير مرغوب في أسواق الصادر نسبة لاحتوائه على نسبة عالية من الألياف. لذلك فقد تم استجلاب بعض الأصناف المرغوبة عالمياً من جنوب أفريقيا ، وقد شملت هذه الأصناف تومي أتكنز ، كنت ، كييت ، هادن وسنسيشن. أجريت التجربة بمشتل الكاملين ، ولاية الجزيرة ، خلال الفترة من يونيو 2008 حتى مايو 2011م لمعرفة تأثير أبعاد الزراعة والتقليم على النمو الخضري ومكونات الانتاج والانتاجية  ونوعية الثمار لهده الأصناف المستوردة مقارنة بالصنف المحلى أبوسمكة. زرعت الأشجار على مسافات 5x5 م و10x 10 م وتم تقليمها بثلاثة طرق للتقليم على النحو التالي : تقليم على فرعين وتقليم على ثلاثة أفرع وتقليم القمم النامية للأفرع وغير مقلمة للمقارنة. استخدم تصميم القطع المنشقة بثلاث مكررات، حيث اسندت القطع الرئيسية لأبعاد الزراعة والقطع الفرعية لطرق التقليم. اظهرت النتائج أن مسافات الزراعة 10x10م اعطت معنوياً أفضل نمو خضري وأكبر عدد الثمار للشجرة الواحدة بالمقارنة مع 5x5م فى كل  المواسم. أبعاد الزراعة  5x5 م اعطت معنوياً أعلى عدد للثمار وأعلى انتاجية للهكتار نسبة للعدد الكبير من الاشجار فى الهكتار. تقليم أشجار المانجو لثلاثة أفرع أعطى معنوياً أعلى انتاج يليه التقليم لفرعين ثم تقليم القمة وأدنى انتاجية كانت فى الاشجار غير المقلمة. الأصناف المستوردة اعطت معنوياً أفضل نمو خضري وأعلى انتاجية وأفضل نوعية للثمار بالمقارنة مع الصنف المحلي أبوسمكة. خلصت الدراسة إلى أنّ الاصناف المستوردة تومي اتكنز وكنت وكيت هى أصناف واعدة يمكن زراعتها فى السودان بطريقة الزراعة المكثفة وتقليمها سنوياً للحصول على أعلى انتاج من الثمار عالية الجودة.